Vaccination coverage of children with rare genetic diseases and attitudes of their parents toward vaccines. Issue 3 (3rd March 2016) - Esposito, Susanna; Cerutti, Marta; Milani, Donatella; Menni, Francesca; Principi, Nicola
Abstract: Despite the fact that the achievement of appropriate immunization coverage for routine vaccines is a priority for health authorities worldwide, vaccination delays or missed opportunities for immunization are common in children with chronic diseases. The main aim of this cross-sectional study was to evaluate immunization coverage and the timeliness of vaccination in children suffering from 3 different rare genetic diseases: Rubinstein-Taybi syndrome (RSTS), Sotos syndrome (SS), and Beckwith-Wiedemann syndrome (BWS). A total of 57 children with genetic diseases (15 with RSTS, 14 children with SS, and 28 with BWS) and 57 healthy controls with similar characteristics were enrolled. The coverage of all the recommended vaccines in children with genetic syndromes was significantly lower than that observed in healthy controls (p < 0.05 for all the comparisons). However, when vaccinated, all of the patients, independent of the genetic syndrome from which they suffer, were administered the primary series and the booster doses at a similar time to healthy controls. In comparison with parents of healthy controls, parents of children with genetic diseases were found to more frequently have negative attitudes toward vaccination (p < 0.05 for all the comparisons), mainly for fear of the emergence of adverse events or deterioration of the underlying disease. This study shows that vaccination coverage is poor in pediatric patients with RSTS, BWS, and SS and significantly lower than that observed in healthy children. These results highlight the need for educational programs specifically aimed at both parents and pediatricians to increase immunization coverage in children with these rare genetic diseases.